KEPUASAN MASYARAKAT TERHADAP KINERJA PEGAWAI RUMAH SAKIT UMUM DAERAH PAMBALAH BATUNG AMUNTAI - irza setiawan (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2018)
This research is mandatory on the basis of the enactment of Law Number 25 Year 2009 on public services, which is then reaffirmed in Provincial Regulation Number 4 year 2013 on public service and Governor Regulation Number 064 year 2014 on the Implementation of Public Service, through its continuous line of apparatus to improve the quality of public services provided. Methods This study uses a quantitative approach, with which the technique of collecting data using questionnaires, observation and documentation, while the answer form in the questionnaire consists of four choices of answers that indicate the level of service satisfaction, ie from not good to good. Result of Research on Satisfaction of Public to Performance of Public Pambalah Batung Amuntai Hospital, The lowest element of service is disciplinary of service officer that is 2,87, while the highest is Clarity of Service Officer, Justice of Getting Service and Fairness of Service Cost is 2,98. The results of research on the performance measurement of Pambalah Batung Amuntai Hospital, if associated with Public Satisfaction Index (IKM) get a value of 72.5 which means entering the category of satisfaction value